The relationship between dividend policy and firm value within Qatari banks - Huda Alenazi (18103309) (2019)
Dividend policy refers to the policy pertaining to the amount paid to shareholders of a company from the total financial budget as a return on their investment. This amount varies depending on the interest of shareholders, cash flow requirements of the company, and many other factors. Dividend policy can affect firm value due to its impact on the cash flow of the company. In this study, the first of its kind in Qatar, we investigated the effect of dividend policy on the firm value of Qatari banks in Qatar Stock Exchange. For this purpose, five banks (Qatar National Bank (QNB), Qatar Islamic Bank (QIB), Masraf Al-Rayan Bank (MARB), International Bank of Qatar (IBQ), and Commercial Bank of Qatar (CBQ)) were selected to find the significance of the correlation between dividend policy and firm value. The study was conducted in three distinct phases. The first phase included the quantitative analysis of the financial parameters of the five selected Qatari banks in which information about their recent five-year (2013–2017) dividend payments and firm values was obtained from their annual financial reports. Then, regression analysis was conducted in SPSS Statistics software. The second phase included the qualitative assessment of the results obtained from the first phase. To support this phase with expertise feedback, a director and a senior official were invited from two banks that showed a significant correlation in their financial parameters of dividend payments and firm values. They were asked about their policies to strengthen the firm value while keeping the interest of shareholders. The third phase included a detailed investigation of the results obtained from both the quantitative and qualitative studies, and the findings were compared with those reported previously in the literature. The research findings suggest that dividend policy has a very strong positive correlation for MARB, a strong positive correlation for QIB, a negative correlation for CBQ, and an irrelevant correlation for QNB and IBQ. Other Information Published in: QScience Connect License: https://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.5339/connect.2019.5